Max Kade Institute Friends Newsletter, Vol. 13, no. 4, Winter 2004 - Petty, Antje; Louden, Mark L.; Kurdylo, Kevin M.; Haese, Elfrieda Bergmann; Saylor, Nicole; Kluge, Cora Lee (Max Kade Institute for German-American Studies, 2004)
Contents: "Conference Explores Tales of Immigration" --- "Directors' Corner: MKI Resources Attracting Researchers" --- "Friend's Profile: Family Letters Inspired Ritsche to Write Novel" --- "Speaking of Language: Elias Molee and the Dream of an International Language" --- "Milwaukee's German-American Taverns in the 1940s" --- "Luxembourg-American Cultural Center in Ozaukee County" --- Collection Feature: Sehen Sie Amerika! Photographic Portfolios in German" --- "Book Review: Finding a German-American Family's Treasure in Milwaukee. A Mystery Novel for Children" --- "German-American Symposium in Bielefeld."
Quarterly Newsletter of the Max Kade Institute for German-American Studies, University of Wisconsin-Madison
Keywords: Milwaukee (Wis.)--History--20th century; German Americans--Wisconsin; Luxembourg Americans; Storytelling; Taverns; German Americans--Emigration and immigration--History--19th century; Wisconsin--Ozaukee County; Max Kade Institute for German-American Studies; German language--Influence on English; United States--History--19th century; German Americans